2018
DOI: 10.1007/s00464-018-6578-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel real-time optical imaging modalities for the detection of neoplastic lesions in urology: a systematic review

Abstract: Background Current optical diagnostic techniques for malignancies are limited in their diagnostic accuracy and lack the ability to further characterise disease, leading to the rapidly increasing development of novel imaging methods within urology. This systematic review critically appraises the literature for novel imagining modalities, in the detection and staging of urological cancer and assesses their effectiveness via their utility and accuracy. Methods A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…A systematic review was conducted by Brunckhorst et al [23]. However, the systematic review was superficial in reviewing CLE's performance in diagnosing bladder cancer, as only one study was included, which reported a proper effect estimate of diagnostic study in the form of sensitivity and specificity [23]. On this basis, the current study attempts to re-explore the performance of CLE in diagnosing bladder cancer, which has never been comprehensively reported before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review was conducted by Brunckhorst et al [23]. However, the systematic review was superficial in reviewing CLE's performance in diagnosing bladder cancer, as only one study was included, which reported a proper effect estimate of diagnostic study in the form of sensitivity and specificity [23]. On this basis, the current study attempts to re-explore the performance of CLE in diagnosing bladder cancer, which has never been comprehensively reported before.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review was conducted by Brunckhorst et al [23]. However, the systematic review was superficial in reviewing CLE's performance in diagnosing bladder cancer, as only one study was included, which reported a proper effect estimate of diagnostic study in the form of sensitivity and specificity [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some optical biopsy techniques, including optical coherence tomography (OCT) and confocal laser endomicroscopy (CLE), involve specific wavelengths of light and cystoscopy in dynamic real-time images of tissue for the surveillance of BCa [19,20]. Sonn et al TURBT combined with PDD can maximize the tumor resection rate to reduce the recurrence of BCa.…”
Section: Optical Biopsy Techniquesmentioning
confidence: 99%
“…Some optical biopsy techniques, including optical coherence tomography (OCT) and confocal laser endomicroscopy (CLE), involve specific wavelengths of light and cystoscopy in dynamic real-time images of tissue for the surveillance of BCa [19,20]. Sonn et al suggested that CLE is an effective aid to cystoscopy using dye fluorescein and light from a Cancers 2022, 14, 3181 4 of 33 488 nm laser fiber optic source to provide real-time dynamic images of malignant cells and normal tissues [21].…”
Section: Optical Biopsy Techniquesmentioning
confidence: 99%
“…Generally, the detection of bladder cancer is performed using white light cystoscopy, which has a limited sensitivity (62%-82%) and specificity (43%-98%) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%